The tripod in the dunny : a study of Patrick White's sylleptic habits - Merrington, David John (Department of English Language and Literature, 2016)
This thesis is a study of relations between aspects of Patrick White's prose style and his perception of a moral equivocation that is entailed in the construction of identity and in the making of fiction. Chapter One presents examples of White's sylleptic style. The virtuosity of the figure is seen to reflect the discursive puissance of a detached and ironic narrative stance. His habitually ironic perspective is ascribed to his apparent sense that human life is governed by fiction, and that such governance is morally equivocal. The chapter concludes with the specification of gossip as a malicious social discourse which, for White, also reflects the practice of narrative fiction. In Chapter Two the analogy between fiction and gossip is developed. The discourse of repute is seen to exercise a perverse and vicarious dominance over its object. This governance by a morally equivocal discourse is considered to illustrate White's habitual apprehension of a universally ironic dispensation under which the human subject exists. The role and the conduct of authorship is examined as the "voice" which governs and articulates such a dispensation. Aspects of M.M. Bakhtin's theory of carnival are adduced, in Chapter Three, to the analysis of-narrative irony. The figure of syllepsis is considered as a stylistic formula for the carnivalesque. The concept of a reactionary "counter-carnival" is formulated, and is used to examine the equivocal energies of White's ironic dispensation. Chapter Four focuses on the carnivalesque dialectic between the orthodox and the grotesque "other". "Illicit knowledge" of the grotesque is seen to be cognate with the discourse of repute and gossip, and the artist is found to be guilty of vicarious appropriations. Chapter Five is an extended analysis of The Twyborn Affair as White's allegory 'of fiction. The chapter is in two parts: the first focuses on the discursive means by which the· fiction of "Eudoxia Vatatzes" is constructed. The flaws in such "authorship" are examined, and this "text" is seen to be a vulnerable and unreliable narrative structure. The second part traces the development of Eddie Twyborn as a fictional "text", through his personae as a jackeroo and as Eadith Trist the brothelkeeper. The Coda comprises brief illustrations, from Three Uneasy Pieces, of Patrick White's last thoughts on authorship.